Diare Dan Asi Eksklusif Dengan Kejadian Stunting Pada Anak Usia 2-3 Tahun Di Wilayah Kerja Puskesmas Bilalang. - Rudolf B. Purba; Phembriah S. Kereh; Anggriani Tabisi (Jurnal GIZIDO, 2019)
Indonesia is a developing country that has many nutritional problems, one of which is chronic nutritional problems in children under five in Indonesia who experience chronic nutritional problems, namely stunting. Stunting is a chronic condition of a child's poor linear growth, as seen from (TB / U <-2 SD). This study aims to determine the history of diarrheal disease and exclusive breastfeeding with the incidence of stunting in children aged 2-3 years in the Work Area of ​​the Bilalang Health Center, Kotamobagu Utara District, Kotamobagu City. This type of observational research with cross sectional approach. The study aims to determine the relationship between the history of diarrheal disease and exclusive breastfeeding with the incidence of stunting. The sampling technique is the Probability Sampling technique. The results of this study showed no significant relationship between the history of diarrheal disease and exclusive breastfeeding with the incidence of stunting in children aged 2-3 years in the Bilalang Health Center Work Area, Kotamobagu Utara District, Kotamobagu City. Conclusion there is no relationship between the history of diarrheal disease and exclusive breastfeeding with the incidence of stunting in children aged 2-3 years in the Work Area of ​​the Bilalang Health Center, Kotamobagu Utara District, Kotamobagu City.